Pengembangan Usaha Ekspor Lidi Nipah BUMDes Bina Mandiri Muara Badak Dalam Meningkatkan Pendapatan Masyarakat Desa Muara Badak Ulu - Meli Dwi Fadilah; Parno Parno; Yovanda Noni (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
This research is based on the background that the economic income of the people of Muara Badak Ulu Village is a micro-scale community economic activity that can be managed by the community and the village government. Factors that influence the increase in economic income of the people of Muara Badak Ulu Village are the development model of the export business of lidi nipah BUMDes fostered independently, the economic income of the community and the obstacles of SME lidi nipah which make it increase the income of the people of Muara Badak Ulu Village.This study aims to determine the development of export businesses for independent-assisted BUMDes in increasing the economic income of the people of Muara Badak Ulu Village. This type of research is descriptive qualitative. The methods used in the study are observation, wawancaea, and documentation. The object in this study is bumdes Bina Mandiri in Muara Badak Ulu Village. The results showed that the model of developing the lidi nipah export business of BUMDes Bina Mandiri in Muara Badak Ulu Village can be seen from the form of success in helping to improve the economic standards of the community in forming a lidi nipah work program consisting of aspects of competition, resources, technology, institutions, and financial institutions. Judging from the economic income of the community in the business of lidi nipah business, it is useful to increase the standard of living of the community where the welfare of the community can provide world happiness and the happiness of the afterlife and be kept away from the evil of their creatures. Then the income generated can meet the needs of his daily life with a profit of around Rp. 20,000,000 (Twenty Million Rupiah) per year. With exports in the form of making broomsticks, mats, and so on, as much as approximately 89 tons per year. The obstacles faced by smes are volatile due to bad weather that makes the palm trees and nipah trees fail to harvest. Therefore, BUMDes helps find nipah land in other villages that are ready to be harvested so that their business can run smoothly. Keywords: Lidi Nipah Export Business Development Model, Community Economic Income, and Lidi Nipah SME Barriers